2017
DOI: 10.1016/j.ijrobp.2017.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Stereotactic Ablative Radiation Therapy for Renal Cell Carcinoma Extracranial Metastases

Abstract: Purpose Renal cell carcinoma is refractory to conventional radiation therapy but responds to higher doses per fraction. However, the dosimetric data and clinical factors affecting local control (LC) are largely unknown. We aimed to evaluate the safety and efficacy of stereotactic ablative radiation therapy (SAbR) for extracranial renal cell carcinoma metastases. Methods and Materials We reviewed 175 metastatic lesions from 84 patients treated with SAbR between 2005 and 2015. LC and toxicity after SAbR were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 26 publications
3
42
0
Order By: Relevance
“…In the clinical setting, dose escalation has also been shown to overcome radioresistance in RCC tumors: Zelefsky and colleagues reported 3-year LC of 88% following SBRT with high fractional doses for extracranial RCC metastases, while LC dropped to only about 20% when lower doses were used (30). A few other reports have also revealed LC rates of about 80-90% for extracranial SBRT in RCC patients (5,6,28,29,31,33). However, due to the limited number of RCC patients treated with SBRT, these reports combined data form different metastatic sites of including lung, bone, liver, lymph nodes or even primary RCC tumors (5,6,28,29,31,33).…”
Section: Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the clinical setting, dose escalation has also been shown to overcome radioresistance in RCC tumors: Zelefsky and colleagues reported 3-year LC of 88% following SBRT with high fractional doses for extracranial RCC metastases, while LC dropped to only about 20% when lower doses were used (30). A few other reports have also revealed LC rates of about 80-90% for extracranial SBRT in RCC patients (5,6,28,29,31,33). However, due to the limited number of RCC patients treated with SBRT, these reports combined data form different metastatic sites of including lung, bone, liver, lymph nodes or even primary RCC tumors (5,6,28,29,31,33).…”
Section: Toxicitymentioning
confidence: 99%
“…However, some RCC patients are medically inoperable due to reduced performance status or comorbidities and some pulmonary metastases are technically not accessible or resectable. For these patients, stereotactic body radiotherapy (SBRT) which utilizes highly conformal ablative local doses to the tumor while sparing surrounding organs, has shown encouraging results (5,(28)(29)(30). However, available reports concerning SBRT for RCC metastases have pooled heterogeneous data from various tumor locations (lung, bone, lymph node, brain, liver, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-comparative retrospective series on SBRT for RCC-bone metastases report local control rates of 70-90% at one or two years, using different fractionation regimens [40][41][42][43][44][45]. Other series including non-bone metastases find similar LCRs [34,35,[46][47][48][49][50]. In a recent systematic review of mainly non-comparative series, the weighted LCR for extracranial RCC-metastases was 89% [22].…”
Section: Local Controlmentioning
confidence: 99%
“…After two years their LCR was 100%, but 64% had progressed at other sites [34]. Another large study reported significantly better local control in patients treated with curative versus palliative intent, but the numerical difference was not large (95% versus 88%) and overall survival data were not provided [35]. There are no comparative studies on SBRT versus metastasectomy, the latter being considered standard therapy though without a proven survival advantage [6].…”
Section: Overall Survivalmentioning
confidence: 99%